Vertically edge-oriented graphene on plasma pyrolyzed cellulose fibers and demonstration of kilohertz high-frequency filtering electrical double layer capacitors. (January 2019) - Islam, Nazifah; Hoque, Md Nadim Ferdous; Li, Wenyue; Wang, Shu; Warzywoda, Juliusz; Fan, Zhaoyang
Abstract: High-frequency electrochemical capacitors or electrical double layer capacitor (HF-ECs) with large capacitance were developed from edge-oriented graphene (EOG) nanosheets perpendicularly grown around carbonized cellulose microfiber (CMF) sheets. Binder-free EOG/CMF electrodes were fabricated in a one-step 5-min plasma-enhanced chemical vapor deposition process, where cellulose fiber sheets were rapidly pyrolyzed by high-temperature plasma, while EOG simultaneously formed on the developing CMFs. Owing to combined unique characteristics of both EOG and CMF, such facilely produced electrodes exhibit excellent performance in terms of both high frequency response and high capacitance density. In aqueous electrolyte cells, 10 μm thick EOG/CMF electrode exhibits an areal capacitance of 1.07 mF cm −2 at 120 Hz along with a frequency of 13.8 kHz at −45° phase angle. ∼3 V organic electrolyte cells show an areal capacitance of 0.49 mF cm −2 at 120 Hz, and a frequency of 1.47 kHz at −45° phase angle. Developed HF-ECs were successfully applied in practical applications as ripple current filter in line-frequency AC/DC conversion, and as pulse power storage/smoother in environmental energy harvesting for self-powered micro devices. Graphical abstract: Image 1